Adipokines regulate the development and progression of MASLD through organellar oxidative stress - Zhao, Ke; Zhang, Heng; Ding, Wenyu; Yu, Xiaoshuai; Hou, Yanli; Liu, Xihong; Li, Xinhua; Wang, Xiaolei (Hepatology communications, 2025)
The prevalence of metabolic dysfunction-associated steatotic liver disease (MASLD), which is increasingly being recognized as a leading cause of chronic liver pathology globally, is increasing. The pathophysiological underpinnings of its progression, which is currently under active investigation, involve oxidative stress. Human adipose tissue, an integral endocrine organ, secretes an array of adipokines that are modulated by dietary patterns and lifestyle choices. These adipokines intricately orchestrate regulatory pathways that impact glucose and lipid metabolism, oxidative stress, and mitochondrial function, thereby influencing the evolution of hepatic steatosis and progression to metabolic dysfunction-associated steatohepatitis (MASH). This review examines recent data, underscoring the critical interplay of oxidative stress, reactive oxygen species, and redox signaling in adipokine-mediated mechanisms. The role of various adipokines in regulating the onset and progression of MASLD/MASH through mitochondrial dysfunction and endoplasmic reticulum stress and the underlying mechanisms are discussed. Due to the emerging correlation between adipokines and the development of MASLD positions, these adipokines are potential targets for the development of innovative therapeutic interventions for MASLD management. A comprehensive understanding of the pathogenesis of MASLD/MASH is instrumental for identifying therapies for MASH.